Multiple Piloleiomyomas : A Report Of 4 Cases - Sharma Rajeev; Bajaj A. K (Wolters Kluwer Medknow Publications, 1997)
Piloleiomyomas are uncommonly reported tumours in Indian literature. The classical tenderness often helps in diagnosis. Multiple lesions are usually seen in familial cases. Our cases had multiple lesions but were non-familial. Response to nifedipine was encouraging.